REPRODUCTIVE HEALTH EDUCATION EARLY PREVENTION OF SEXUAL VIOLENCE WITH PHANTOM MEDIA AT TK ALIF CENTER INTEGRATED - Rosa Purwanti; Septi Fitrah N; Mudhawaroh Mudhawaroh (Pakis Journal Institute, 2023)
Kindergarten is a very effective educational forum to introduce children to reproductive health from an early age. The impact of low public understanding of reproductive health causes various health, economic, social, and crime problems that occur increasingly rampant throughout the country. Provide Health Education on proper reproductive health, and limb recognition for each student, using phantom media. Community service activities run in an orderly and smooth manner, material on reproductive health is delivered by the head of the community service, and body recognition practices can be touched on or not guided by Community Service Members and students. The participants in this community service activity consisted of teachers and students TK Alif Integrated as many as ± 23 people. The participants were enthusiastic and communicate with the speakers. Reproductive health education based on phantom media in early childhood is very useful and more effective than counseling without media, because it can significantly increase children's knowledge and understanding as well as skills and awareness.